Kingdom's edge - Black, Chuck (Sisters, Or. : Multnomah Publishers, 2006)
Cedric of Chessington's life of poverty and despair is forever changed when a mysterious stranger arrives in his city and reveals he is a Master of the Sword and there to train Cedric.
Young Adult
Young Adult
Keywords: Knights and knighthood -- Fiction; Knights and knighthood -- Fiction; Allegories; Christian fiction; Allegories; Christian fiction